Associative Meaning in Minangkabau Song`s lyrics: Semantic Approach - Syamsul Bahri; Fauziah Khairani Lubis (Hasanuddin University, 2021)
This study was conducted to investigate the Associative Meaning used in Minangkabau song's lyrics. It used a descriptive qualitative method to analyze the data by using textual analysis to elaborate the song's lyrics and the data was taken from Minangkabau songs such Japuiklah Denai, Kasiah tak sampai, Cinto ka Uda, and Pantai Padang. All songs were popularized by Elly Kasim, concerning individual experiences of her love like what was reported in Dialog Programme YouTube of Edriana Views, dialogue among Elly Kasim, Edriana, and her friends. The findings showed all types of Associative Meaning were found in such Minangkabau songs. The most frequent type was Social Meaning 41%, Affective Meaning 29.7%, Connotative Meaning 21,8%, Reflected Meaning 4.7%, Collocative Meaning 3,1%. Social Meaning is mostly found to convey or introduce custom aspects of the writer's background of life. One of the Cultural aspects is the use of kinship stated in Minangkabau song’s lyric. Affective Meaning is stated to explore the writer’s feeling in the song's lyrics. Connotative meaning is also found to beautify Minangkabau song's lyrics by stating an indirect meaning and it has artistic values. Reflected Meaning shows the style or existence of harsh meaning in the song's lyrics. Collocative Meaning is found to reveal the song's lyrics in the same environment.